Communication Strategy of Relationship Chat Account Manager in Managing the Follower - Anna Gustina Zainal; Toni Wijaya; Andy Corry Wardhani (Ikatan Sarjana Komunikasi Indonesia, 2021)
Each social media account created by users has its own purpose and meaning,. That is to attract the sympathy of the audience, Just like in real world, humans cannot live without socializing and interacting each other. This research was designed to find out the communication strategy of social media account managers in managing followers. This study used an interactional communication strategy with qualitative descriptive method. The results showed that the communication strategy used to manage the